2022
DOI: 10.3390/cancers14143407
|View full text |Cite
|
Sign up to set email alerts
|

TNFRSF1A Gene Polymorphism (−610 T > G, rs4149570) as a Predictor of Malnutrition and a Prognostic Factor in Patients Subjected to Intensity-Modulated Radiation Therapy Due to Head and Neck Cancer

Abstract: Background: Malnutrition is a nutritional disorder observed in 52% of patients with head and neck cancer (HNC). Malnutrition is frequently related to the increased level of proinflammatory cytokines. In turn, ongoing inflammation is associated with increased catabolism of skeletal muscle and lipolysis. Tumor necrosis factor α (TNF-α) is a proinflammatory cytokine that plays a pivotal role in the development of malnutrition and cachexia in cancer patients. The aim of the study was to assess the relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Sharma et al found that TNF-α -238 AA and -308 AA genotype in patients with end-stage renal disease exhibited a higher susceptibility to malnutrition and higher levels of TNF-α ( 31 ). Homa-Mlak et al investigated the association between single nucleotide polymorphisms in the TNF-α-610 T > G (rs4149570) gene and the development of malnutrition in HNC patients receiving radiotherapy ( 23 ). They found that the TT genotype possessed a higher risk of malnutrition (OR = 5.05; p = 0.0350) and was also associated with critical weight loss (OR = 24.85; p = 0.0009).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Sharma et al found that TNF-α -238 AA and -308 AA genotype in patients with end-stage renal disease exhibited a higher susceptibility to malnutrition and higher levels of TNF-α ( 31 ). Homa-Mlak et al investigated the association between single nucleotide polymorphisms in the TNF-α-610 T > G (rs4149570) gene and the development of malnutrition in HNC patients receiving radiotherapy ( 23 ). They found that the TT genotype possessed a higher risk of malnutrition (OR = 5.05; p = 0.0350) and was also associated with critical weight loss (OR = 24.85; p = 0.0009).…”
Section: Discussionmentioning
confidence: 99%
“…As SNPs do not change during the disease process, in addition, the risk of malnutrition is individual and does not appear to be related to demographic or most clinical factors. Therefore, it has been proposed that the risk of malnutrition may be related to genetic predisposition ( 23 , 24 ). TNF-α is probably the most characteristic cytokine in malnutrition.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations